2008
DOI: 10.1111/j.1469-7580.2007.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatographic investigation of pancreatic duct system and pancreaticobiliary malformation

Abstract: To clarify the anatomy of the pancreatic duct system and to investigate its embryology, we reviewed 256 pancreatograms with normal pancreatic head, 81 with pancreas divisum and 74 with pancreaticobiliary maljunction. Accessory pancreatograms were divided into two patterns. The long-type accessory pancreatic duct forms a straight line and joins the main pancreatic duct at the neck portion of the pancreas. The short-type accessory pancreatic duct joins the main pancreatic duct near its first inferior branch. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…The three subtypes of pancreas divisum were identified in the present MRCP study, which is similar to the findings of Adibelli et al 7 and Kamisawa and Okamoto. 21 In the present cadaveric study, ansa pancreatica (type V) was observed in one cadaveric specimen, but not radiologically. It was reported radiologically in the MRCP (1.2%) by Adibelli et al 7 Hayashi et al 22 found that it has a significant association with recurrent acute pancreatitis.…”
contrasting
confidence: 61%
“…The three subtypes of pancreas divisum were identified in the present MRCP study, which is similar to the findings of Adibelli et al 7 and Kamisawa and Okamoto. 21 In the present cadaveric study, ansa pancreatica (type V) was observed in one cadaveric specimen, but not radiologically. It was reported radiologically in the MRCP (1.2%) by Adibelli et al 7 Hayashi et al 22 found that it has a significant association with recurrent acute pancreatitis.…”
contrasting
confidence: 61%
“…The development of the human pancreas embryology is complex, resulting in many different congenital pancreaticobiliary variations [ 1 , 3 ]. The human pancreas develops from the ventral and dorsal pancreatic buds whose fusion causes the anastomosis of the pancreatic ducts at the 6th to 7th embryological week [ 1 , 8 , 9 , 15 , 16 ]. The ventral pancreatic duct and the distal part of the dorsal pancreatic duct are anastomosed and form the MPD of Wirsung, while the proximal part of the dorsal pancreatic duct becomes the APD of Santorini [ 1 , 9 , 15 ].The major pancreatic duct opens into the ampulla of Vater, and the minor pancreatic duct opens into the minor papilla [ 1 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many of the articles that we found in the literature, the authors did not use this kind of classification; instead, they used the term “normal pancreatic duct” to describe a pancreas that could be classified as type 1, 2, or 3. Therefore, we could not separate the patients between these three groups, and we presented them as a unique type of normal pancreatic duct anatomy ( Tables 2 and 3 , [ 3 - 5 , 7 , 9 - 14 ]). In addition, some authors used a different type of pancreatic duct classification (e.g., Bang et al (2006) [ 7 ]; Bulow et al (2014) [ 5 ]), and the correspondence was made according to the descriptions they used for the type of pancreatic duct they studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have prospectively studied the anatomy of the pancreatic duct system using endoscopic retrograde pancreatography [6,7,8,9]. To achieve optimal visualization, several pancreatograms of the head of the pancreas were taken with the patient in the prone or slightly oblique position.…”
Section: Methodsmentioning
confidence: 99%